Optimizing Fertility in Primary Ovarian Insufficiency: Case Report and Literature Review - Piedade, Kensuly C.; Spencer, Hillary; Persani, Luca; Nelson, Lawrence M. (Frontiers in Genetics, 2021)
Primary Ovarian Insufficiency (POI) is a clinical spectrum of ovarian dysfunction. Overt POI is a chronic disorder characterized by oligo/amenorrhea and hypergonadotropic hypogonadism before age 40 years. There may be significant morbidity due to: 1) psychological and psychiatric disorders related to the loss of reproductive hormones and infertility; 2) reduced bone mineral density; and 3) increased risk of cardiovascular disease related to estrogen deficiency. Presently with standard clinical testing a mechanism for Overt POI can only be identified in about 10% of cases. Now, recent discovery of new mechanisms permits an etiology to be identified in a research setting in 25% to 30% of overt cases.(Rossetti et al., 2017) The most common genetic cause of overt POI is premutation in FMR1. The associated infertility is life altering. Oocyte donation is effective, although many women prefer to conceive with their own ova. Surprisingly, the majority who have overt POI still have ovarian follicles detectable (70%). The major mechanism of follicle dysfunction in overt POI has been histologically defined by a prospective NIH study: inappropriate follicle luteinization due to the tonically elevated serum LH levels. A trial of physiologic hormone replacement therapy, clinically proven to suppress the elevated LH levels in these women, may improve follicle function and increase the chance of ovulation. Here, we report the case of a woman with overt POI diagnosed at age 35 years. To attempt pregnancy, she elected a trial of intrauterine insemination (IUI) in conjunction with follicle monitoring and physiologic hormone replacement therapy. She conceived on the eighth cycle of treatment and delivered a healthy baby. Our report calls for a concerted effort to define the best methods by which to optimize fertility for women who have POI.